Artificial Intelligence Based DAM Monitoring and Water Quality Measurement System - Hemalatha, L; Sakthivel, S (International Journal of Computer Sciences and Engineering, 2014)
In order to enhance reliability and safety procedures of the dam, it is very important to gather dam behavior data in real-time monitoring system. The main aim to implement the automatic dam monitoring based on 8051 microcontroller is mainly designed to precisely measure, store and transmit various parameters output to the computer server. These sensor systems monitor the condition of the dam automatically by sensing water acidity level, water conduction level, pressure and temperature level of the dam .The sensor output is signal conditioned and it is digitized by using an analog to digital converter. The microcontroller controls the operation of the ADC and the digital output of the ADC is transferred to the input port of the microcontroller. Then the transmitter section transmits that digital output to the receiver section. When the water level of the dam goes above a threshold level the microcontroller automatically turns ON the Buzzer to indicate the critical condition. In the receiver section will be having GSM Modem to send the condition that presents in the dam to the supervisor and nearby people of the dam. The communication between transmitter and receiver is zigbee for the real time application for high reliability.